Foreign experience in professional development of private detectives - Stanislav, Denysiuk; Ivan, Motyl; Inna, Vartyletska; Nataliia, Symonenko; Volodymyr, Korotaiev (Cuestiones Políticas, 2020)
The objective of the article is to analyze international experience in the professional development of private detectives, in order to implement some positive aspects in Ukrainian law. The methodological basis of the research was articulated in a set of general and special scientific methods of scientific knowledge, a saber: historical comparative method and legal method, dialectic, induction method, comparative and legal method, formal and legal method. Based on the analysis of international experience, the education problems of private detectives, as well as those that recycling and advanced training features, whose study is necessary for the full development of the institution of the activity of private detectives in Ukraine, reveals the revelation of modern services for the training of private detectives in Ukraine. In the conclusions, the authors pay special attention to specialists in the activity of private detectives in several countries, where private detectives have a wide range of opportunities and their activity is actually compared to the activity of law enforcement. Finally, the requirements are proposed for candidates for the position of private detective, as well as for the program of their training.